Pemulihan Psikososial Anak Pasca Gempa: Strategi Trauma Healing Berbasis Komunitas - Sutikno, Ari Yudha Caesar; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2025)
Earthquakes, as sudden natural disasters, can cause serious psychological trauma, especially in children. This article aims to describe the implementation of community-based trauma healing to support the emotional recovery of children affected by earthquakes. Based on direct experiences in volunteer work and field observation at post-earthquake shelters, community-based approaches using social activities, art, and play were found to be effective in reducing trauma symptoms. Trauma healing serves not only to address short-term emotional distress, but also to help restore children’s sense of safety and hope in post-disaster environments.